Fertilizer doses for jute cultivation after onion harvest - Rani Debnath, Manika; Mahabubul Islam, Md.; Ayub Khan, Md.; Akter, Sharmin; Mukul Mia1, Protap Narayan Nandi, Md. (International Journal of Advanced Geosciences, 2020)
An experiment was conducted to evaluate the fertilizer dose for jute cultivation at the field after harvesting of onion at Gangabordi and Talma, Faridpur during 2017 with five treatments with different level of Urea, Triple Super Phosphate, Muriate of Potash and Gypsum. The result revealed that the treatment of higher doses of fertilizer gave the statistically significant highest fibre (2.76t/ha) yield whereas treatment of lower doses of fertilizer gave the lowest fibre yield (2.40 t/ha) but the Benefit Cost ratio from different treatment showed statistical non significance. From the view of economic profitability, farmers may use no fertilizer at their field during jute cultivation where previous crop was onion.Â Â Â